Integrated management improves emerging coastal industries and ecological restoration with the participation of social capital - Shusheng, Xu; Jingqian, Xie; Mianrun, Chen (Frontiers in Marine Science, 2023)
In this study, we aimed to provide policy advice that supports continuous ecological restoration and coastal economic development. Our analysis indicated that insufficient funds and space are the main problems in mangrove restoration projects in China and Southeast Asian countries. The average cost of mangrove restoration projects in China has been RMB 999,000/ha, leaving a mangrove restoration funding gap of RMB 1,500,000,000/year. Another common problem of emerging industries is insufficient space, another is a lack of subsidies. Learning from the positive experiences of inland areas and Southeast Asian countries, we propose a plan for integrated management that improves emerging marine industries and ecological restoration with the participation of social capital. We also designed a time road map to achieve the plan based on a target area. A SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis showed that the plan is a win-win model plan, which may generally meet the needs of the local government, such as ecological restoration, pollution control, industrial upgrades, and income improvement. Finally, we suggest that governments should strengthen cross-department coordination, improve current sea area use policies, and strengthen associated publicity attempts.